Evaluación técnica y económica en vivienda modelo sostenible utilizando paneles fotovoltaicos para reducir el consumo energético - Cedeño Jordan, Livingston Ariel (2025)
Focused on the creation of sustainable housing through the application of photovoltaic systems. The main objective is to explore and demonstrate how this technology reduces energy consumption in homes by efficiently and adaptively using air flows, natural light, temperature, and solar energy, studying how the automation of these systems improves energy efficiency without compromising the comfort of residents. Our proposal focuses on various areas, such as the implementation of photovoltaic panels, cross-ventilation to optimize air capture, and its effect on reducing energy use. This initiative responds to the growing need for sustainable alternatives in the construction industry, with the goal of minimizing environmental impact. Furthermore, this design not only increases energy efficiency but also has the potential to become a model for other industries, promoting a greener and more affordable future.